Human capital and successful academic spin-off - Bettina Müller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
Academic spin-offs are one way in which employability of university graduates is reflected. Using the ZEW spinoff-survey, this paper studies empirically the impact of human capital on the success of academic spinoffs founding in knowledge and technology intensive sectors. The focus is thereby on the composition of human capital which is described according to whether or not the founders have studied several subjects and whether or not they all come from the same research establishment. Additionally the impact of having founded as a team is analyzed. Success is measured by employment growth. The findings suggest that it is advantageous to found within a team, but that the human capital composition both for single entrepreneurs and team foundations is rather irrelevant.
Keywords: C12; M13; L25; 330; Higher Education; Human Capital; Entrepreneurship; Spin-off